Variation in the distribution of quantitative characteristics of the illiterate population in Baghdad governorate for the years 1997, 2016 and 2019 - Hamad, Athraa Abd; Salman, Nada Najeeb (Al-Adab Journal, 2021)
The study is concerned with the quantitative characteristics of the qualitative and age composition of the illiterate population in the province of Baghdad at the district level and according to the 1997 census, and the Food Security and Vulnerability Survey of the Household in Iraq for the year 2016, as well as the statistics of the executive body for eradicating illiteracy for the year 2019. The study relied on the illiterate population from the age of ten Years or more and over the decimal age groups, the study showed that the gender ratio of the illiterate population for the three years was low at the governorate level, reaching (43 males for every 100 females) for the year 1997, then there was a slight increase in this percentage at the governorate level for the years 2016 and 2019 compared to the previous years. Their ratio reached (44 males for every 100 females), which means that every forty-four illiterate males correspond to one hundred illiterate females, and this is due to females being affected more than males by social, economic, political and other factors that have an impact on the spread of illiteracy in a society. As for the age structure of the illiterate population, the study showed that the highest percentage of the illiterate population came within the age group of the elderly (60 and over), and for the three years 1997, 2016 and 2019 at the governorate level, it reached for each year (28.9%, 30.2%, and 30%), respectively, and the reason for the high rate of illiterates and over those years was the result of the abolition of the Literacy Law No. (92) of 1978 by virtue of the dissolved Revolutionary Command Council Resolution No. (439 of 1987, and everything related to the abolition of popular schools to eradicate illiteracy, and the reason for this decision was for military tactical purposes, as the student moved to the People's Army during the first Gulf War (1980-1988).